(untitled) (International Journal of Current Engineering and Technology, 2014)
View the important role of the surface for the bricks aesthetic and mechanical characteristics and its products. this study has been focus of the use of copper filings waste resulting from industrial processes (metals machining) to paint the brick surface of the standard bricks product of one brick plants at different ranging copper filings from (1-6%) of the glazed mixture. Furnace was used under the temperature of 12000C for glazed mixture. two stages were used to get the desired product, the first layer of white paint of TiO2, and then followed by a final layer of copper filings, results show the gradient of surface color of the golden yellow of the dark brown and flexural resistance of the bricks product was 0.1- 0.6 J. The two types of brick glazed were denoted by (A) and (AB) that include of partial glazed by copper layer, and fully glazed of double layers by TiO2 and copper layers respectively.